Expanding Caenorhabditis elegans research: First Latin American Worm Meeting. Issue 1 (2nd January 2017) - Carrera, Inés; Calixto, Andrea; Salinas, Gustavo
ABSTRACT: From February 22nd to 24th, 2017, in Montevideo, Uruguay, Latin American scientists working with C. elegans gathered to share their research at the First Latin American Worm Meeting. This event was supported by the International Worm Community and included the presence of 17 speakers from North America, Europe and Israel. Martin Chalfie, who supported the initiative from the beginning, gave a keynote talk. This meeting greatly helped consolidate the Latin American Worm Community. The next meeting will take place in Rosario, Argentina in 2020.